Analisis Penerapan Cash Management System (CMS) sebagai Upaya Pencegahan Fraud dalam Sistem Pembayaran BPPKAD Wonosobo - Shandy Ramadhani Okta Kharisma; Yulida Army Nurcahya (Jurnal Ekonomi dan Bisnis Digital, 2026)
The implementation of non-cash payment systems in regional financial management aims to enhance transparency, accountability, and efficiency in government financial transactions. One of the systems utilized is the Cash Management System (CMS), which uses banking technology to facilitate electronic financial transactions. This study aims to analyze the implementation of CMS as an effort to prevent fraud in the payment system at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) of Wonosobo Regency in 2026. The study employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, and then analyzed using a SWOT analysis approach. The results indicate that the implementation of CMS improves transparency and transaction efficiency while strengthening internal control, thereby minimizing the potential occurrence of fraud.